Recovery Enhancement with Application of FAWAG for a Malaysian Field - Tunio, Saleem Qadir (Maxwell Scientific Organization, 2012)
At present, petroleum engineering has become economics based field hence all efforts are being made to make sure that we squeeze out the last drop of oil from the reservoir. Field A, one of Malaysian oil field is a strong candidate for Enhanced Oil Recovery (EOR) which was producing for more than 15 years. Here, in this research, we are focusing one of the currently demanded techniques for better oil recovery. There are various water alternating gas “WAG”techniques which have proven to be the best answer in improving the recovery. Foam can also be added in water alternating gas technique to improve the sweeping mechanism and cut off the gas production which is termed as Foam Assisted Water-Alternating Gas (FAWAG). In this study, a detailed application of FAWAG has been done on crude oil sample from Field A. Results shows that FAWAG tends to address all recovery related problems efficiently where as foam has been seen to address the problems by assisting other enhanced oil recovery techniques and proved that foam assistance has given better recovery.